Natural Poisoning by Xanthium cavanillesii in Cattle in the Southern Region of the State of Rio Grande do Sul - Barbosa, Antônio Amaral; dos Santos, Ederson; Klaus, Rosana; Rabassa, Viviane Rohrig; Soares, Mauro Pereira; Correa, Marcio Nunes (Acta Scientiae Veterinariae, 2020)
Background: Poisoning by Xanthium spp. plants are important causes of deaths of cattle in the state of Rio Grande do Sul. This plant has as toxic principle a triterpenoide glycoside that acts inhibiting the transport of adenosine diphosphate and adenosine triphosphate across the mitochondrial membrane, responsible for causing acute liver failure. Clinical signs occur within hours of ingesting the plant. However, the knowledge of the metabolic disorders that these animals suffer are poorly described, so the objective of the reports is to describe an outbreak of spontaneous intoxication by Xanthium cavanillesii and demonstrate the clinical, metabolic and anatomopathological changes of a poisoned bovine. Case: An 8-month-old male bovine, Aberdeen Angus breed, was sent to the Veterinary Hospital of Clinics of Federal University of Pelotas (HCV-UFPel). The animal came from a property located in the southern region of Rio Grande do Sul, belonged to a herd of 506 animals, of which 258 were nulliparous cows and 248 calves, in total 92 died, being 20 cows and 62 calves in a period of 3 days. The clinical course ranged from 3 to 72 h and was characterized by neurological signs (pedaling movements, opisthotonus and motor incoordination), sternal decubitus, muscle tremors, apathy, anorexia, hypersalivation, dehydration, tenesmus and death. In the field where the animals were, there was the present of Xanthium cavanillesii in the dicotyledonouns sprouting phase, with signs of ingestion. During the clinical examination of the animal sent to the hospital, sternal decubitus, muscle tremor, motor incoordination, apathy, anorexia, hypersalivation and opisthotone were observed, heart rate of 60 beats per minute, respiratory rate of 15 movements per minute, 2 ruminal movements incomplete at every 2 minutes, moderate dehydration and temperature of 37.9º C. For laboratory exams, blood samples were collected in vacuum tubes with 10% EDTA, to perform blood count with hemoparasite research, and without anticoagulant, to perform serum biochemistry tests, liver and kidney function. Highlighting the increase in liver enzymes (aspartate aminotransferase, gamma glutamyltranferase and alkaline phosphatase), hypoglycemia, elevation of total bilirubin and direct bilirubin, hypoalbuminemia, increase in triglycerides with leukocytosis by neutrophilia with regenerative left shift. Due to advanced clinical condition of the animal, was realized euthanasia for post-mortem examination. At necropsy, the main diagnostic macroscopic lesions were an accentuation of the lobular pattern of the organ parenchyma with the appearance of “nutmeg” and centrilobular coagulative necrosis accompanied by congestion and hemorrhages, characterizing a picture of acute liver failure. In addition, X. cavanillesii fruits were detected in the rumen content. Discussion: The diagnosis was based on epidemiological, clinical-anatomopathological, laboratory data and experimental reproduction of the disease in cattle and sheep. Regarding the epidemiological findings, the presence of the plant with signs of ingestion stands out in addition to the absence of other plants capable of producing similar cases on the farm. The metabolic changes described, if analyzed in isolation, do not confirm the diagnosis, but combined with other parameters, it contributes to the assessment and prognosis of the patient, becoming of great importance in elucidating and conducting the clinical condition.